Analisis Karakter Kesabaran Mahasiswa dalam Mengatasi Stress Akademik di Universitas Negeri Medan - Hapni Laila Siregar; Maya Martiza Sari; Muhammad Baihaqi; Idrus Hamonangan Pane; Nadya Viska Harahap; Dina Aulia (CV. ULIL ALBAB CORP, 2024)
This research shows that the majority of Medan State University students experience stress due to task pressure. This research aims to analyze the relationship between the level of patience and academic stress in students at the Faculty of Economics. This research uses qualitative methods with student respondents at the economics faculty. This research also highlights the importance of religious values, especially patience in Islam, in facing life's challenges, including academic stress. The approach was carried out inductively, starting with data coding to identify the main themes that emerged from the questionnaire results. This study was selected through a purposive sampling technique, where they were selected based on certain criteria relevant to the research subject, such as education level, gender, and experience in dealing with academic stress. Data was collected by distributing in-depth questionnaires starting from April 6 2024 to April 10 2024. Thus, from the research results, a significant relationship was found between the level of patience and the level of academic stress in students at the Faculty of Economics. Data analysis shows that students with higher levels of patience tend to have lower levels of academic stress, while those with lower levels of patience tend to experience higher levels of academic stress. This research contributes to the understanding of the factors that influence academic stress and emphasizes the importance of integrating religious values ​​in improving students' well-being and academic achievement, especially in the context of religious life which is rich in moral and spiritual values.